Data-Based and Continuous Evaluation Strategies for Assessing the Quality of Learning in Islamic Education - Muslim; Yuli Supriani; Ika Ratna Rosanti; Andri Setiadi; Ani Apiyani (Universitas Islam Negeri Mataram, 2026)
The quality of learning is a key factor in the success of Islamic education; however, the implementation of learning quality assessment in many Islamic secondary schools still faces a gap between actual practices and expected standards. This study aims to formulate a data-based and continuous evaluation-oriented strategy for assessing learning quality at MTs Mamba’ul Ulum Metro in order to improve teaching effectiveness and academic decision-making. This study employed a descriptive qualitative approach involving teachers, the school principal, and students as research subjects, with data collected through classroom observations, in-depth interviews, and document analysis of assessment records. The findings show that formative and summative assessments have been implemented; however, the use of assessment data for continuous improvement remains limited and has not yet been systematically integrated. The analysis indicates that a strategy based on continuous evaluation and teacher collaboration can improve learning responsiveness, identify students’ learning difficulties more quickly, and strengthen evidence-based quality management. In conclusion, a systematic and data-based assessment strategy not only bridges the gap between actual conditions and expected quality standards but also provides an innovative model that can be replicated in other Islamic educational institutions. Keywords: quality assessment strategy, continuous evaluation, Islamic education, data-based management.